Teachers’ Perception towards Parental Involvement in Their Children’s Education in the Secondary Schools, Temerloh, Malaysia - Mohamad Nor, Reduan (2008)
The research focuses on secondary school teachers’ perception of parental involvement in their children’s education based on Epstein model. The main aim of this study is to explore the secondary school teachers’ perception towards parental involvement in their children’s education. The respondents were comprised of 130 teachers from three selected schools that are located in the district of Temerloh. This study is descriptive in nature. Findings showed that teachers perceived parents need to show involvement in four out of six types of parental involvements in the Epstein model. The four types of parental involvements specified by teachers are parenting, communication, home learning, and collaboration with community. Based on the level of teachers’ satisfaction, generally they were not satisfied with parental involvement in parenting and volunteering activities, but were satisfied with parental involvement in activities of communication and home learning. For school governance activities, generally teachers said that parental involvement in the children’ education involved attending PIBG meeting in schools (61.5%) while less than 50% of teachers’ agreed that parents involved frequently in other activities such as engaged as the schools’ committee and ‘involved in the programmed organized by schools and in revising schools’ curriculum’. While for school collaboration and community activities, majority of the teachers’ perceived that frequency of which school involves outsiders in education is low. The teachers also perceived that problems and the constraints in the parental involvement in their children education in school as due to “being too busy”, “reluctant to get involve”, “lack of knowledge”, “lack of source of money to support activities involving the parents”, “negative attitude”, and “lack of skills”. Based on the comparison of the different ethnics of parents involved in children education, it is shown that the Malay parents’ involvement is high in the activities such as discussing with teachers, encouraging children to attend extra class and co-curriculum activities, giving ideas and energy, and receiving comments and critics on their children. Chinese parents perceived to be more interested in sending children to tuition classes, giving donation to schools and buying extra reference books. Indian parents and other ethnics perceived as having the lowest level of involvement in the respected activities too. The highest method of interaction between parents and schools according to the teachers are through letters, followed by telephone and face-to-face interaction. Other methods such as e-mail, facsimile and SMS are very rarely used. Besides that, teachers perceived that in terms of community’s involvement in education, the highest is through government department while the involvement from other agencies is still low. This research implies that more has to do be done to increase the level of parental involvement in their children education in schools, including planning and implementing more effective programmers.